Substrate-Modulated Reductive Graphene Functionalization - Schäfer, Ricarda; Weber, Konstantin; Kolesnik-Gray, Maria; Hauke, Frank; Krstic, Vojislav; Meyer, Bernd; Hirsch, Andreas (Angewandte Chemie International Edition, 2016)
Covalently functionalizing mechanical exfoliated mono- and bilayer graphenides with λ-iodanes led to the discovery that the monolayers supported on a SiO2 substrate are considerably more reactive than bilayers as demonstrated by statistical Raman spectroscopy/microscopy. Supported by DFT calculations we show that ditopic addend binding leads to much more stable products than the corresponding monotopic reactions as a result of the much lower lattice strain of the reactions products. The chemical nature of the substrate (graphene versus SiO2) plays a crucial rol
Keywords: functionalised grapnene; substrate interactions; chemical reactivity